2009
DOI: 10.1121/1.3129127
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language differences in cue use for speech segmentation

Abstract: Two artificial-language learning experiments directly compared English, French, and Dutch listeners' use of suprasegmental cues for continuous-speech segmentation. In both experiments, listeners heard unbroken sequences of consonant-vowel syllables, composed of recurring three-and four-syllable "words." These words were demarcated by ͑a͒ no cue other than transitional probabilities induced by their recurrence, ͑b͒ a consistent left-edge cue, or ͑c͒ a consistent right-edge cue. Experiment 1 examined a vowel len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
215
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(237 citation statements)
references
References 45 publications
(27 reference statements)
17
215
4
1
Order By: Relevance
“…For example, Warner, Otake, and Arai ( 2010 ) argued that the crosslinguistic use of rising F0 found in Japanese and French (Welby, 2007 ) as well as Korean (Kim, 2004 ) is due to the universally applicable auditory-perceptual salience of F0 rise. Phrasefi nal lengthening has also been claimed to be a universally applicable segmentation cue, as English, Dutch, and French listeners use the fi nal lengthening cue in lexical segmentation (Tyler & Cutler, 2009 ).…”
mentioning
confidence: 99%
“…For example, Warner, Otake, and Arai ( 2010 ) argued that the crosslinguistic use of rising F0 found in Japanese and French (Welby, 2007 ) as well as Korean (Kim, 2004 ) is due to the universally applicable auditory-perceptual salience of F0 rise. Phrasefi nal lengthening has also been claimed to be a universally applicable segmentation cue, as English, Dutch, and French listeners use the fi nal lengthening cue in lexical segmentation (Tyler & Cutler, 2009 ).…”
mentioning
confidence: 99%
“…In particular, as discussed in the introduction, the fact that Korean listeners perceive (phonetically poorer) unreleased stops better than (phonetically richer) released stops in processing non-native speech has provided a concrete example of a situation where phonological experience overrides phonetic richness in non-native speech perception (Cho & McQueen, 2006). The language-specificity of speech perception has also been observed in lexical segmentation of unfamiliar artificial languages or non-native languages-e.g., the use of language-specific phonotactics (Weber & Cutler, 2006) and rhythmic/prosodic cues (Cutler & Otake, 1994;Kim et al, 2012;Tyler & Cutler, 2009) in processing non-native speech. The results of the present study therefore appear to be in contrast to the generally observed dependency that listeners have on their phonological knowledge in the perception of unfamiliar or non-native speech.…”
Section: Discussionmentioning
confidence: 99%
“…Listeners had to identify the words in the test phase. This paradigm has been shown to be effective in testing effects of specific cues in the speech signal without recourse to any prior lexical knowledge and it has also revealed listeners' use of native segmentation cues in lexical segmentation of these unfamiliar, non-native languages (e.g., Bagou et al, 2002;Kim et al, 2012;Saffran et al, 1996;Tyler & Cutler, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations